Nonprogression with avelumab treatment associated with gains in quality of life in metastatic Merkel cell carcinoma. (February 2018) - Kaufman, Howard L; Hunger, Matthias; Hennessy, Meliessa; Schlichting, Michael; Bharmal, Murtuza
Aim: To assess the association between tumor response and health-related quality of life (HRQoL) in patients with metastatic Merkel cell carcinoma treated with the anti-PD-L1 avelumab.Materials & methods: Phase II single-arm trial (NCT02155647) data of 88 patients were analyzed. Correlations between percentage reduction in tumor size and change from baseline in Functional Assessment of Cancer Therapy – General (FACT-G), FACT – Melanoma (FACT-M) and EuroQol-5 Dimension scores were calculated. HRQoL and utility by tumor response (per the Response Evaluation Criteria In Solid Tumors version 1.1) was estimated.Results: Tumor shrinkage correlated positively with patients' change from baseline in the FACT-M total (0.364 [95% CI: 0.050–0.607]) and subscale scores. Differences in HRQoL and utility between nonprogressive disease and progressive disease were clinically relevant.Conclusion: In patients with metastatic Merkel cell carcinoma, nonprogression during treatment with avelumab correlated with gains in HRQoL. Trial registration: This study is a planned exploratory analysis conducted on data collected in Part A of the JAVELIN Merkel 200 trial. This trial was registered on 2 June 2014 withClinicalTrials.gov as NCT02155647.